Repetitive head impacts in youth football: Description and relationship to white matter structure - Nilsson, K. J.; Flint, H. G.; Gao, Y.; Kendrick, L.; Cutchin, S.; Pentecost, R.; Pardue, K. (Sports Health: A Multidisciplinary Approach, 2019)
Background: Few studies have examined white matter with diffusion tensor imaging in 8- to 12-year-old collision sport (CS) athletes.